(untitled) (Texas Journal of Engineering and Technology, 2022)
To put it another way, cloud computing is a method that allows for the rapid movement of resources such as servers, storage, networks and services from one location to another utilizing little administration effort. For the most part, it is a large-scale distributed computing architecture that is based on dynamically-scalable and managed virtualized processing power, storage, applications and services. The cloud presents to users as a single point of access for all of their anticipated computing requirements. Customers may keep their data in the cloud and use the on-demand software from the cloud without having to worry about local infrastructure. When it comes to computers, security and reliability are two of the most pressing concerns. A revolutionary new platform has been developed to solve the issues of security vulnerability and data center dependability in this study. The Cloud Storage system employs data redundancy strategies including replication, RAID, and erasure code to give tools at any time (reliability). Cloud computing systems may be installed in one of three ways. Public, private, and even a mix of all three have existed. There is already a private cloud at which the cloud is developed, managed by the particular enterprise in the proposed system. Replication and RAID’s drawbacks were mitigated by the inclusion of Erase Code in the private cloud system’s design. Low storage costs, normalization costs, fast processing speeds, ease of data center recovery in the event of a disaster, and assistance in setting up a secure cloud storage system are just some of the benefits it provides